Dynamic Neural Representations: An Inferential Challenge for fMRI. Issue 7 (July 2019) - Ghuman, Avniel Singh; Martin, Alex
Abstract : Measures of brain activity with high temporal resolution have shown that the information represented in a single brain region undergoes dynamic changes on the scale of milliseconds. This dynamic process presents a unique inferential challenge to low temporal resolution neural measures, such as BOLD fMRI. Potential solutions for fMRI requiring further investigation and development are discussed.